Optimasi Portofolio Saham LQ45 (2021-2025): Pendekatan Single Index Model dan Implikasi Alokasi Aset - Nabila maharani; Esty Apridasari; Atika Lusi Tania; Witantri Dwi Swandini (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
The increase in domestic investor participation in the Indonesian capital market, reaching 20.3 million SID by 2025, is not always accompanied by stable stock market performance. This situation presents challenges for investors in determining an optimal stock portfolio with a measurable level of risk. This study aims to construct an optimal LQ45 stock portfolio based on return and risk levels. Furthermore, this study aims to determine the proportion of fund allocation and investment portfolio execution for investors. The research method used is descriptive quantitative, utilizing secondary data in the form of LQ45 stock closing prices, the Jakarta Composite Index (JCI), and Bank Indonesia interest rates for the period August 2021 to July 2025. The sample selection was conducted using purposive sampling technique to obtain 25 stocks that were consistently listed in the LQ45 index during the study period. The results showed that there were 10 stocks included in the optimal portfolio based on the Single Index Model. These stocks are INDF, MEDC, BBNI, PGAS, BMRI, BBCA, ITMG, ICBP, ANTM, and UNTR with different fund allocation proportions. The optimal portfolio produced an expected rate of return of 1.42% with a portfolio risk of 0.19%. This study shows that the Single Index Model is effective in forming an optimal LQ45 stock portfolio. This model can be used as a basis for investment decision making by considering the balance between risk and return.